Comparison of three maximal anaerobic running test protocols in marathon runners, middle-distance runners and sprinters - Vuorimaa, T.; Hakkinen, K.; Vahasoyrinki, P.; Rusko, H. (International Journal of Sports Medicine, 1996)
Three modifications of the maximal anaerobic running test (MART) were compared in sprinters (Spr, n = 5), middle-distance runners (Mid, n = 5) and marathon runners (Mar, n = 6). The MART1, MART3 and MART5 consisted of n sets of 1.20-s, 3.20-s and 5.20-s runs, respectively, on a treadmill with 40-s recovery between the runs and 100-s recovery between the sets. In each MART the velocity of the first set of runs was 3.0 m.s-1 and the slope 4 degrees. Thereafter, the velocity was gradually increased by 0.38 m.s-1 for each consecutive set until exhaustion. After each set and after exhaustion fingertip blood samples were taken to determine lactate concentration and three counter-movement jumps (CMJ) were performed. Maximal (Pmax) and submaximal (P4mM) running power in each MART was expressed as the oxygen demand (ml.kg-1.min-1) of the runs. In MART1, Mar had a significantly lower Pmax than Mid or Spr (mean +/- SD; 97.8 +/- 5.4 vs. 121.0 +/- 4.4 vs. 119.2 +/- 5.4 ml.kg-1.min-1), while in MART3 the groups did not differ significantly, and the sprinters were unable to perform MART5. Mar, Mid and Spr attained the lower Pmax the more runs per set in MART (p < 0.01). Mar had the higher peak blood lactate the more runs each set consisted of (p < 0.001). In Mid and Spr, the peak blood lactate did not differ significantly between the MARTs but was significantly higher than the corresponding peak blood lactate of the marathon runners. Pmax in MART1 correlated positively with maximal 20-m sprinting speed on a track and with CMJ height (p < 0.001, n = 16) but negatively with VO2 max (p < 0.001, n = 16) while in MART3 no significant correlations were found. It was concluded that the n.1.20-s protocol should be used to measure the maximal anaerobic power of all runners. However, in ong-distance runners more runs per set may be needed to evaluate their anaerobic capacity.